Carboidratos solúveis, redutores e não redutores, de dez clones de mandioca (Manihot esculenta Crantz) cultivados em Minas Gerais - Feitosa Teles, F F; L de Oliveira, Maril; J da Silveira, Américo; D Fabris, José; M Batista, Cid (Revista Ceres, 2025)
Ten cassava cultivars, cultivated in the state of Minas Gerais, Brazil, were analysed for soluble carbohydrates, reducing and non-reducing sugars. The analyses were carried out colorimetrically by the Teles’Reagent after extraction with ethanol 50% (v/v).